Alcoholic liver disease: a synopsis of the Charles Lieber's Memorial Symposia 2009-2012 - Neuman, Manuela G.; Mueller, Sebastian; Seitz, Helmut K. (Alcohol and alcoholism, 2014)
This paper is based upon the ‘Charles Lieber Satellite Symposia’ organized by Manuela G. Neuman at each of the 2009–2012 Research Society on Alcoholism (RSA) Annual Meetings. The presentations represent a broad spectrum dealing with alcoholic liver disease (ALD). In addition, a literature search (2008–2013) in the discussed area was performed in order to obtain updated data. The presentations are focused on genetic polymorphisms of ethanol metabolizing enzymes and the role of cytochrome P4502E1 (CYP2E1) in ALD. In addition, alcohol-mediated hepatocarcinogenesis, immune response to alcohol and fibrogenesis in alcoholic hepatitis as well as its co-morbidities with chronic viral hepatitis infections in the presence or absence of human deficiency virus are discussed. Finally, emphasis was led on alcohol and drug interactions as well as liver transplantation for end-stage ALD.
Gesehen am 21.08.2020